Determinants of Stunting in The Under-five in West Nusa Tenggara Province with Multilevel Binary Logistic Regression - Rambi, Ananda; Budyanra, Budyanra (Jurnal Matematika, Statistika dan Komputasi, 2024)
Stunting is a form of malnutrition in children that is still a health problem in Indonesia, especially in NTB Province. Based on the results of the SSGI, the prevalence of stunting in children under five years of age in NTB Province was 32.7 percent, up 1.3 percent compared to the previous year. This value has not reached the threshold of 20 percent and the national target of 18.4 percent. This puts NTB Province in the fourth highest position in Indonesia. In 2022, NTB Province recorded the highest percentage in Indonesia for children under six months who received exclusive breastfeeding, which was 79.69 percent. However, the prevalence of stunting in toddlers in NTB Province is still very high. Between districts/cities in NTB Province, there is a fairly high disparity in the prevalence of stunting in children under five years of age. This shows the influence of regions or households so that there is a disparity in the prevalence of stunting in children under five years of age. This study aims to describe the incidence of stunting in toddlers in general and analyze the variables that influence it and its tendencies in NTB Province in 2022 using a multilevel binary regression model. The results of the study showed that the variables of toddler gender, toddler age, history of toddler pneumonia, maternal education level, access to clean drinking water sources, access to proper sanitation, and GRDP per capita had a significant effect